An investigation of the socio-cultrural and economic dynamics of the displacement of inhabitants of the Tokwe-Mukosi valley after the floods of 2014 - Mashawi, Audrey (Midlands State University, 2019)
The aim of this study was to examine the socio-cultural and economic dynamics of displacement of the inhabitants of Tokwe-Mukosi valley after the floods of 2014. In February 2014 nearly 3500 families living at Tokwe and Mukosi village abandoned their ancestral land following heavy flooding from the incomplete Tokwe-Mukosi dam. The dam was constructed to boost agriculture production in Masvingo province thus to improve food security in the country. However, it resulted in the displacement of the villagers of the valley. The displacement program brought a lot of challenges to the relocated families as compared to Chivi life. They lost their sources of livelihood and created a dependency syndrome whereby resettled families began to depend on donations. The research unveiled that the relocation resulted in disintegration of family tie, destruction of graves, shrines and undermining of cultural values of the local people. Women were marginalised as a result of the displacement. Their community gardens were destroyed. They suffered more than men especially at Chingwizi transit camp. The research concluded that the displacement program impoverished the relocated families. The flood victims were poorly taken care of by the government. They were relocated without compensation.